Soka Gakkai International Quarterly Magazine (Japan : Soka Gakkai International, 2015)
This magazine aims to highlight initiatives and perspectives on peace, education and culture and to provide information about the Soka Gakkai International activities around the world.
Feature -- Essay -- People -- Dialogue -- Around the world -- On Vocation -- Buddhism in daily life.
Includes bibliographical references.
Keywords: FORESTS; ENVIRONMENT; NATURE; RAINFORESTS; AMAZON